Identifying Brúnanburh : ón dyngesmere : the sea of noise - Kirby, John R. (Access archaeology., 2019)
In this study the author uses topographic references found in the manuscript of the poem 'Brúnanburh' to try and locate the 'site' of this momentous battle. The first references were maritime then latterly landscape leading to field-names which have a more stable base than the constantly changing place-names.